ANALISIS MANAJEMEN KREDIT DALAM MENINGKATKAN LIKUIDITAS DAN PROFITABILITAS PADA INDUSTRI PERBANKAN (KASUS PADA BANK BUMN YANG TERDAFTAR DI BEI) - Dina Lestari; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Provision of credit facilities is always the risk of a will arise, it is necessary for credit management so that risk can be minimized. If the credit management implemented not good it appears a credit risk which will cause the credit becomes problematic which will affect the liquidity and profitability of the Bank. The purpose of this study (1) To determine and analyze the Credit Management to see the level of Non Performing Loan (NPL) in the BUMN Banks (2) To determine and analyze the liquidity and profitability has been achieved in the BUMN Banks. With the research method used is quantitative descriptive. The method of data collection used secondary data such as financial statements, the data in the form of interviews were also used as additional information to obtain data that is spoken. Data analysis using financial ratios Non Performing Loan (NPL) for measuring credit management, Loan to Deposit Ratio (LDR) to measure liquidity, and Return On Assets (ROA) to measure profits.Results of research conducted showed that the ratio of Non Performing Loan (NPL) in BUMN Banks during the period of 2011-2014 the BRI, Mandiri, BNI and BTN Bank are in a state of "healthy" that do not cross the line provisions of 5% -8%. Liquidity and profitability has been achieved by BUMN Banks the show is liquidity in 85% <ratio <100%, or the ratio <50% for Bank BRI, Mandiri and BNI is in a "healthy" while BTN Bank in the "healthy enough" while profitability at BUMN Banks in a "very healthy" and are at above 0.5 <ROA≤1,25%.Keywords: Credit Management, Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Return on Assets (ROA)